Using CHETAH to estimate lower flammable limit, minimum ignition energy, and other flammability parameters. Issue 4 (8th November 2014) - Britton, Laurence G.; Harrison, Benjamin Keith
<x xml:space="preserve">Abstract</x> Britton discovered that with increased "net heat of oxidation" (ΔHox), the maximum flame temperatures of CH and CHO fuels in air increase linearly while flame temperatures at the lower flammable limit (LFL) decrease linearly. Maximum flame temperature is a major factor determining the combustion rate of optimum fuel‐air mixtures and relationships were found between ΔHox and "optimized" flammability parameters such as minimum ignition energy. The LFL is the fuel concentration needed to attain the lower limit flame temperature; since less fuel is needed to attain a smaller flame temperature, the LFL varies inversely with ΔHox. Simple expressions derived between ΔHox and parameters commonly used in process safety were previously published in this journal. The commercially available computer program "CHETAH™" now solves these expressions and outputs the flammability parameters plus the internally generated thermodynamic data used in the solutions. This article updates the original expressions together with new findings and explanatory material. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 314–328, 2014